Tracking Advances in Access to Electricity Using Satellite-Based Data and Machine Learning to Complement Surveys - Dhorne, Milien (World Bank, Washington, DC, 2021)
Access to electricity is widely considered a major determinant of socioeconomic development. But despite long-standing efforts to expand access, 789 million people remained without electricity in 2018. Accurate and reliable data to keep track of electrification efforts must be the first step toward achieving universal access. Monitoring access with the finest granularity and taking into account local socioeconomic characteristics enable a realistic depiction of electrification progress. Such data can be used to plan efficient and robust energy access policies and programs, to raise public awareness of the urgency of action, to sustain the pace of electrification, and ultimately to connect the hardest-to-reach populations. In addition to identifying where efforts should be targeted, high-resolution data are needed to show which electricity supply options are most relevant. Remote sensing techniques and geographic information systems have revolutionized data collection by providing a range of location-specific information that was not previously accessible. The use of standardized geospatial tools and methods has made it possible to offer countries technical assistance and operational support for the development of national electrification strategies, least-cost electrification plans, and country-based investment prospectuses that combine grid, mini-grid, and off-grid technologies.